Is there a universally acknowledged human right to water? : an analysis of obligations under international, regional and national law : a case study of Germany and South Africa - Penkalla, Michaela (Department of Public Law, 2016)
The purpose of this dissertation is to assess whether or not there is a universal human right to water. The problem of water scarcity and high death rates due to a lack of access to clean water is still prevalent across the globe today, making it hard to believe that a human right to water is still not codified in international law. This dissertation analyses international as well as national law to assess whether a human right to water is universally acknowledged by the international community despite not being codified. It is argued, that there is still no explicit universal human right to water in international law. However, this dissertation acknowledges that a human right to water does exist as a derivate right, which is almost universally acknowledged. As a derivative right, it is, however, not as equally strong as explicitly acknowledged rights in the core international human rights instruments. This dissertation also provides a brief overview of corporate involvement under the human right to water. An assessment is made as to whether or not international law imposes direct obligations and responsibilities on companies. It is argued in this dissertation that companies have a particular responsibility for the implementation of the human right to water despite states remaining the primary subjects responsible.